Narrativas de histórias de vida de idosas lésbicas: interseccionalidade entre velhice, gênero e sexualidade - Dantas, Anne Joyce Lima (2021)
This research intends to understand the life forms and expressions of sexuality of elderly lesbians in the Fortaleza city, trying to describe how these women negotiate their performances and search for recognition, seeking to reflect on the aging process of elderly lesbians in contemporary times, their social impacts and identifying fragments of emancipation based on new identity manifestations linked to the aging of women and their expressions of sexualities. The relevance of this research is affirmed by contributing to the visibility of elderly lesbian women, proposing to deepen the discussions on aging, its expressions and subversions of sexualities and identities. This research was inspired by ethnography for observing immersion with a group of elderly lesbian women. This research is separated as follows: 01) a discussion about the intersectionality between old age, gender and sexualities, presenting some problematizations about the body, sexual and identity subversion in old age; 02) systematic review of the literature in CAPES Journals, discussing productions that discuss lesbian aging; 03) Presentation of the narrative as a method; 04) description of the experience with a group of elderly lesbian women and 05) discussion about the narratives of elderly lesbians about their lives, bringing themes related to the beginning of lovers and sexual experiences with women; current relationships; lesbian sexuality and aging, and the lesbian aging process (body and old age). From the narratives presented by the participants of this research, it is necessary to discuss the aging process, deviate from the homogeneous way in which it is approached, considering the diversity of identities and expressions of sexualities that involve old age, so that it is possible to propose social policies that cover old age in a plural way.